Karakteristik Legislatif dan Ketepatwaktuan Anggaran: Studi Empiris pada Pemerintah Daerah di Indonesia - Muhtar (MANAJEMEN DEWANTARA, 2022)
This study aims to examine the effect of local legislative characteristics on the timeliness of local government budgets in Indonesia. Using secondary data from the authorized institutions, this study generates 2032 observations covering all local governments in Indonesia during 2015-2018 that were analyzed using multiple linear regression. The research findings show that most local governments in Indonesia have been able to validate the Local Revenue and Expenditure Budget (APBD) on time, although there are still several local governments that are late by exceeding the deadline of the APBD validation date. Furthermore, the analysis results reveal that legislative political competition has a negative effect on local government budgeting timeliness while legislative size has a positive effect. However, this study finds no significant effect of legislative gender representation considering the relatively low political representation of women in the Regional People's Representative Council (DPRD). From the analysis results obtained, this study emphasizes that the DPRD as the people’s representation must always maintain the quality of supervision in the preparation of the budget even though there is political competition and differences in interests. The people should also increase the representation of women in the DPRD to support equality and support the implementation of DPRD functions. In addition, local governments must also have an adequate number of DPRD members as needed. Thus, local governments can fulfill the timeliness of the APBD validation as a form of local government financial accountability. Keywords: local government; budgeting timeliness; political competition; gender representation; legislative size